Cloud-assisted rendering support for mobile online gaming Part C - Lam, Chun Lih (2014)
Cloud computing had changed the outlook of IT industry, which enable the utilization of software and hardware in a virtual space instead of physical hardware. With the adoption of the cloud computing, the organizations can focus their capital onto other areas of their company instead of being tied down in the IT costs in the organization. Besides cost efficient due to elimination on costly hardware or engaging IT professionals, it provides other advantages such as “Almost” unlimited storage as limitation of the storage space no longer limits to the amount of hardware the organization have but the amount of cloud storage the organization bought through the cloud storage providers. Not only these, cloud computing provides easy access to information as long as there is internet connection. This easy to access feature not lets you move beyond time zone and geographic location issues.